Zaufanie jako element etyki zakładów ubezpieczeń na życie - Wieteska, Stanisław (Annales. Etyka w Życiu Gospodarczym, 2009)
The issue of mutual trust is an important element in each economic activity, especially in the global market economy. It also concerns insurance activity. Entering into contracts with clients, a life insurance company becomes a public trust institution. The long-term responsibility lies on the insurance company side.The act of 23 March 2003 on insurance activity sets forth that insurance institutions are obligated to systematically inform their insured clients about contract commitments. The paper shows some examples of clients losing trust in insurance companies. It also defines public trust and the basic factors influencing public trust in life insurances.